Okupacja budynku PZPR w Poznaniu - Kaczmarek, Filip (Komunizm: System - Ludzie - Dokumentacja, 2023)
The purpose of the text is to analyze the circumstances surrounding the occupation of the Polish United Workers’ Party’s building in Poznań on the 17th and 18th of January 1990. The building was occupied by students from the Independent Students’ Association. It became one of the symbols of the end of the Party’s activity in this city. The historiography regarding the turn of the 1980s and 1990s often overlooks the episodes of occupying or picketing the Party’s buildings by students from the Independent Students’ Association (Poznań, Katowice, Częstochowa, Kraków, Białystok, Łódź, Toruń). Some researchers only describe similar actions organized by the Confederation of Independent Poland (Konfederacja Polski Niepodległej, KPN), most likely because it was the first organization to start such activities, as early as in October 1989. In Poznań, students from the Adam Mickiewicz University were the initiators and organizers of the occupation of the building. The research method used is the analysis of documents, memories of participants, and media coverage.